HISTORICAL AND CULTURAL CONTEXTS OF FEMININE CHARACTERS IN LITERATURE - Milikova Maftuna Akmaljanovna Samarqand davlat chet tillari universiteti magistranti Ilmiy rahbar: PhD. dotsent Rustamova Adash Eshankulovna (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article delves into the intricate interplay between historical and cultural contexts and the portrayal of feminine characters in literature. Drawing upon a diverse range of literary works spanning different epochs and regions, the study examines how societal norms, cultural values, and historical events shape the depiction of women in fiction. Through a nuanced analysis, it explores the evolution of feminine archetypes, from traditional roles of motherhood and domesticity to more complex and empowered representations. By scrutinizing the historical backdrop against which these characters are situated, the article sheds light on the ways in which authors both reinforce and subvert gender stereotypes, reflecting the prevailing ideologies of their times. Moreover, it investigates the impact of feminist movements and social change on literary representations of femininity, highlighting the role of literature in challenging established norms and fostering progressive attitudes towards gender equality. Ultimately, this exploration underscores the dynamic relationship between literature, history, and culture in shaping our understanding of feminine identities across time and space.